2016
DOI: 10.1038/mp.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Novel osmotin inhibits SREBP2 via the AdipoR1/AMPK/SIRT1 pathway to improve Alzheimer’s disease neuropathological deficits

Abstract: Extensive evidence has indicated that a high rate of cholesterol biogenesis and abnormal neuronal energy metabolism play key roles in Alzheimer's disease (AD) pathogenesis. Here, for we believe the first time, we used osmotin, a plant protein homolog of mammalian adiponectin, to determine its therapeutic efficacy in different AD models. Our results reveal that osmotin treatment modulated adiponectin receptor 1 (AdipoR1), significantly induced AMP-activated protein kinase (AMPK)/Sirtuin 1 (SIRT1) activation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 35 publications
(26 reference statements)
2
130
2
Order By: Relevance
“…Chrebp and Srebp2 were each appreciably expressed and unaffected by GVAD, but moderately suppressed by Cyp1b1 deletion. Elsewhere, post-translational SREBP activity has been linked to iron homeostasis through AMPK-directed phosphorylation (Huang et al, 2013, Shah et al, 2016), possibly with different effectiveness for the selective pathway mediators.…”
Section: Resultsmentioning
confidence: 99%
“…Chrebp and Srebp2 were each appreciably expressed and unaffected by GVAD, but moderately suppressed by Cyp1b1 deletion. Elsewhere, post-translational SREBP activity has been linked to iron homeostasis through AMPK-directed phosphorylation (Huang et al, 2013, Shah et al, 2016), possibly with different effectiveness for the selective pathway mediators.…”
Section: Resultsmentioning
confidence: 99%
“…Cultured SH-SY5Y cells were transfected with 200 nM siRNA using Lipofectamine 2000 reagent (Invitrogen) for 24 h [24], then the DMEM medium was replaced with glutamate and anthocyanins as indicated in the respective “Methods” section.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, one study on the progression of pancreatic cancer showed that APN can protect pancreatic beta cells against apoptosis via activation of 5′ AMP-activated protein kinase (AMPK), SIRT1, and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1 α ) signaling [28]. Furthermore, modulating the APN receptor 1 (AdipoR1) and inducing AMPK/SIRT1 activation can improve neuropathological deficits in Alzheimer's disease [29]. However, the exact role of SIRT1 in the cytoprotective effects of APN is still not completely understood, especially in cases of stroke.…”
Section: Introductionmentioning
confidence: 99%